CORPORATE GOVERNANCE IN ISLAMIC FINANCE THROUGH THE LENS OF MAQĀṢID AL-SHARI’AH: AN ESG-ORIENTED APPROACH TO SUSTAINABLE DEVELOPMENT - Monira , Nurjahan Akter; Arup , Arnob Debnath; Rainak , Maisha (International Journal of Shari’ah and Corporate Governance Research, 2025)
Islamic finance is grounded in Shariah principles that emphasize ethical conduct, social welfare, and the achievement of the higher objectives of Islamic law (Maqāṣid al-Sharīʿah). At the same time, environmental, social, and governance (ESG) frameworks have become central to global financial markets as tools for promoting sustainability, accountability, and long-term value creation. Despite clear normative overlap between Islamic ethics and ESG principles, their formal integration within Islamic corporate governance remains uneven and underdeveloped, with fragmented standards and limited empirical synthesis. This study examines how Maqāṣid al-Sharīʿah and Islamic corporate governance frameworks can be aligned with ESG principles to support sustainable development in Islamic finance. The study employs a structured review of peer-reviewed journal articles, regulatory standards, and policy documents related to Islamic finance, Shariah governance, ESG frameworks, and sustainable development. The analysis covers international evidence from Islamic banks, takaful operators, and green finance instruments, with particular attention to governance mechanisms such as Shariah supervisory boards and ESG disclosure practices. The results reveal a strong conceptual convergence between Maqāṣid al-Sharīʿah and ESG dimensions, with preservation of life, wealth, and social welfare closely aligned with environmental protection, social responsibility, and governance transparency. Empirical evidence indicates that Islamic financial institutions with stronger Shariah governance structures demonstrate higher ESG performance, particularly in social and governance indicators. In contrast, environmental performance shows a moderate but positive association. The findings suggest that integrating ESG metrics into Shariah-governed corporate structures quantitatively enhances ethical oversight, stakeholder accountability, and alignment with sustainability, reinforcing the role of Maqāṣid al-Sharīʿah as a comprehensive ethical foundation for sustainable Islamic finance. JEL Classification Codes: G15, G34, Q01, Z12.